(3QSGdI GdSdhc Edi edc Gdedhcs - (3bGSe GdMdHjs ((3eMeO Hf efUhQ Hf eMeO Hf CNjGQ s)
(3ChdgG (B:s
(3GdMeO ddg GdPi CgHW HMceI CSQGQ PGJg ef SeGA GdeLO Edi GQV GdWHjYI GdcdjI hChOYgG HbOQJg ai UOa GdfWa s
(3BNQgG (B:s
(3hUdi Gddg Ydi CTQa GdCfHjGA hGdeQSdjf hYdi Bdg hUMHg CLeYjf hGdMeO ddg QH GdYGdejf hdGMhd hdGbhI EdG HGddg GdYdi GdYXje hef jYJUe HGddg abO gOi Gddg UQGW eSJbje GfJgi s
(3GdfSNI HgG MhGTs
(3GdfSNI ebQhAI hYdjgG JUhjHGJs
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , JQeje s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs